Validity and usefulness of the short form of the Drinking Motives Questionnaire Revised (DMQ-R SF) among patients with schizophrenia. (June 2022) - Gierski, Fabien; Benzerouk, Farid; Jeanblanc, Jérôme; Angerville, Bernard; Dervaux, Alain; Kaladjian, Arthur; Naassila, Mickaël
Highlights: We investigated drinking motives among outpatients with schizophrenia. Results supported the psychometric validity of the DMQ-R SF in schizophrenia. Comorbid AUD was not related to any psychotic symptom dimensions and severity. AUD was associated with higher drinking motives and polysubstance use. Higher AUDIT scores were related to high enhancement and coping motives. Abstract: Objective: Drinking motives are considered to be major predictors of alcohol consumption and alcohol-related problems. However, these motives have been poorly investigated in patients with schizophrenia. The aim of the present study among patients with schizophrenia was twofold: 1) assess the validity of the short form of the Drinking Motives Questionnaire-Revised (DMQ-R SF); and 2) investigate the relationship between drinking motives and comorbid alcohol use disorder (AUD). Method: A total of 179 patients with schizophrenia were approached to participate in the study. DSM-5 criteria were used to identify patients with comorbid AUD (AUD+; n  = 42) and non-abstainers patients without comorbid AUD (AUD-; n  = 71). Results: A confirmatory factor analysis conducted on items of the DMQ-R SF for the whole sample revealed adequate goodness-of-fit values, while internal consistency indices were globally satisfactory. Group comparisons revealed higher use of alcohol and other substances, as well as stronger drinking motives among AUD + patients, while groups were comparable concerning clinical features of schizophrenia, including psychotic symptom dimensions and severity. Regression analysis showed that the Alcohol Use Disorder Identification Test score was significantly associated with two internal drinking motives: enhancement and coping. Conclusions: Findings suggest that the DMQ-R SF is a reliable tool for assessing drinking motives among patients with schizophrenia. Enhancement and coping motives seem to play a major role in comorbid AUD among these patients. Community-based and clinical treatment programs should take the drinking motives of dual-diagnosis patients into consideration, in order to improve their outcomes.